KRITIK TRADISI ILMIAH BARAT: MENYOROT FUNGSIONALITAS METODE ILMIAH DALAM PEMBANGUNAN MANUSIA SEUTUHNYA - Syarif, Fajar (Ibn Khaldun University, Bogor, 2017)
This research discusses the development of Western Science, which utters a negative impact in the shaping of society and men as human. The prime factor is the understanding of